When Science Meets Justice: A Case Study on Eyewitness Misidentification and Wrongful Conviction - Urreta Benítez, Facundo A.; Leon, Candela S.; Bonilla, Matías; Garrido, Manuel; Prandi, Micaela; Forcato, Cecilia (The Wrongful Conviction Law Review, 2026)
In 2008, a group of three armed individuals entered a grocery store in the Buenos Aires area. The episode ended tragically with the death of the store owner. A local man, M.A.M., was accused of the crime and sentenced to life in prison. After the conviction, the defense filed an appeal with a higher court. There, legal organizations submitted amicus briefs raising concerns about M.A.M.’s factual innocence. Our team was consulted by Innocence Project Argentina to review the official records, providing a psychological and neuroscientific analysis of the eyewitness identification procedures that may have led to a wrongful conviction. Specifically, we examined the recognition procedures and the statements of key witnesses. Subsequently we presented an amicus curiae with our findings. Here, we discuss the results of that analysis in light of current theories on memory distortion, including reconsolidation, forgetting, and common errors in recognition. In 2022, the Provincial Court of Cassation acquitted M.A.M., citing the lack of reliable evidence to uphold the conviction. The expert report presented by our team was among the materials considered in reaching that decision.